Dogs don't tell jokes - Sachar, Louis, 1954- (London Bloomsbury Publishing Plc, 2007)
Twelve-year-old Gary, known as Goon because of his constant clowning and joke-telling, tries to change his image and make new friends at school.
Elem. School Library Collection
School Library Journal
Wilson's Junior High School
Elem. School Library Collection, March 1998
School Library Journal, June 1998
Wilson's Junior High School, September 1995
Keywords: Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Self-perception -- Juvenile fiction; Friendship -- Fiction; Schools -- Fiction; Self-perception -- Fiction; Friendship -- Fiction; School stories; Self-perception -- Fiction